Private Enterprise and the China Trade Merchants and Markets in Europe, 1700-1750 - von Brescius, Meike (Brill, 2022)
This book examines the European commercial landscape of the early China trade, c.1700-1750. It looks at the foundational period of Sino-European commerce and explores a world of private enterprise beneath the surface of the official East India Company structures. Using rich private trade records, it analyses the making of pan-European markets, distribution networks and patterns of investment that together reveal a new geography of a trading system previously studied mostly at Canton. By considering the interloping activities of British-born merchants working for the smaller East India Companies, the book uncovers the commercial practices and cross-Company collaborations, both legal and illicit, that sustained the growth of the China trade: smuggling, wholesale trading, private commissions and the manipulation of Company auctions.